2012
DOI: 10.1039/c2fo00001f
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of Brassica olerecea and Eugenia jambolana extracts against H2O2 induced cytotoxicity in H9C2 cells

Abstract: This study assesses the efficacy of anthocyanin rich Brassica olerecea leaves (ARCE) and flavonoid rich Eugenia jambolana seed (EJSE) extracts as possible cardioprotective agents against hydrogen peroxide (H(2)O(2)) induced cytotoxicity in H9C2 cells. Presence of ARCE or EJSE resulted in a superior cell viability and cell integrity as revealed by cell viability and lactate dehydrogenase release assays and acridine orange and ethidium bromide staining of control and H(2)O(2) treated H9C2 cells. These extracts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
1
8
0
1
Order By: Relevance
“…The AO/EB staining showed that maximum number of prominent fluorescent red cells following H2O2 induced toxicity of H9C2 cells. The Brassica olerecea and Eugenia jambolana extracts were able to restore the apoptosis cell and fragmented chromatin in H9C2 cells from H2O2 treatment [35]. Similar results were obtained in the present study confirming that sodium selenite and SeNPs significantly protect the ethanol induced apoptosis in H9C2 cells.…”
Section: Selenium and Senps Protect The Cells From Apoptosissupporting
confidence: 94%
“…The AO/EB staining showed that maximum number of prominent fluorescent red cells following H2O2 induced toxicity of H9C2 cells. The Brassica olerecea and Eugenia jambolana extracts were able to restore the apoptosis cell and fragmented chromatin in H9C2 cells from H2O2 treatment [35]. Similar results were obtained in the present study confirming that sodium selenite and SeNPs significantly protect the ethanol induced apoptosis in H9C2 cells.…”
Section: Selenium and Senps Protect The Cells From Apoptosissupporting
confidence: 94%
“…Early studies initiated in our lab had reported ARCE mediated decrement in intracellular oxidative stress and restoration of mitochondrial membrane potential in H 2 O 2 treated H9c2 cells [ 20 ]. Also, safety evaluations had revealed that ARCE was non-toxic to H9c2 cells (10–100 μg/ml) and Swiss albino mice (1000–3000 mg/kg) [ 20 , 31 ]. Keeping these findings as a background, the present study was initiated to decipher the underlying mechanism of ARCE mediated cardioprotection.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a dose-dependent reduction in H 2 O 2 induced cytotoxicity and apoptosis of H9c2 cells clearly implicated at ARCE mediated prevention of apoptotic cascade in oxidatively stressed cells. These results are attributable to the free radical scavenging property of ARCE [ 20 ] that had accounted for reduced cytotoxicity and prevented trigger of apoptotic cascade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The color intensity indirectly refl ects the health of cells and functional mitochondria. [ 26 ] Because of the simplicity and effectiveness of this protocol MTT assay is widely used for assessing cytotoxicity of various therapeutic agents, [27][28][29][30][31] metal complexes, [32][33][34] and nanoparticles. [ 35 ] In our study interaction of ion gel with adherent A549 cells did not account for any mortality till the highest dose (200 μg mL −1 ) (Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%